2015
DOI: 10.4103/0974-9233.151877
|View full text |Cite
|
Sign up to set email alerts
|

Changes in corneal topography and biomechanical properties after collagen cross linking for keratoconus: 1-year results

Abstract: Purpose:To evaluate changes in corneal topography and biomechanical properties after collagen cross-linking (CXL) for progressive keratoconus.Patients and Methods:Collagen cross-linking was performed on 97 eyes. We assessed uncorrected visual acuity (UCVA) and best corrected visual acuity (BCVA). Corneal topography indices were evaluated using placido disc topography, scanning slit anterior topography (Orbscan II), and rotating Scheimpflug topography (Pentacam). Specular microscopy and corneal biomechanics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 34 publications
2
12
0
1
Order By: Relevance
“…In another recent study investigating corneal topographical and biomechanical properties in the 1st year after conventional CXL in 97 eyes and compatible with our results they also reported a significant improvement in UCVA and BCVA values with a significant decrease in CCT and corneal volume without any significant alterations in CH and CRF. However, diversely from our results, they reported a significant decrease in average keratometry value (19). Interestingly, Beckman et al (20) investigated the biomechanical effects of conventional CXL in 29 eyes of 28 patients and reported increased CH values with applanation resonance tonometer but not with ORA.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In another recent study investigating corneal topographical and biomechanical properties in the 1st year after conventional CXL in 97 eyes and compatible with our results they also reported a significant improvement in UCVA and BCVA values with a significant decrease in CCT and corneal volume without any significant alterations in CH and CRF. However, diversely from our results, they reported a significant decrease in average keratometry value (19). Interestingly, Beckman et al (20) investigated the biomechanical effects of conventional CXL in 29 eyes of 28 patients and reported increased CH values with applanation resonance tonometer but not with ORA.…”
Section: Discussionsupporting
confidence: 61%
“…It is theoretically possible to evaluate the corneal biomechanical properties that may occur in the cornea with the ocular response analyzer (ORA) designed to obtain in vivo measurements (14). While several studies report the biomechanical changes after conventional CXL with the ORA device (15)(16)(17)(18)(19)(20)(21), the data about the results of accelerated CXL regarding the biomechanical features of the cornea are limited in the literature (22). In this study, we aimed to investigate the biomechanical and topographic alterations in 12 month period after accelerated collagen CXL treatment among patients with keratoconus.…”
Section: Introductionmentioning
confidence: 99%
“…For our simulations, the range of potential variation of the anterior and posterior corneal curvature in keratoconus after collagen crosslinking surgery (CXL) was defined considering the information reported in previous studies evaluating the outcomes of CXL [ 6 10 ]. The definition of the potential values of r 2c after CXL that could be used in our theoretical simulations was defined according to previous studies reporting changes occurring in such parameter measured using the Scheimpflug imaging technology [ 11 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The definition of the potential values of r 2c after CXL that could be used in our theoretical simulations was defined according to previous studies reporting changes occurring in such parameter measured using the Scheimpflug imaging technology [ 11 13 ]. According to all previous studies revised, the anterior corneal radius ( r 1c ) was found to range in keratoconus after CXL between 5.6 and 8.5 mm, and the posterior corneal radius ( r 2c ) between 4.4 and 7.0 mm [ 6 10 ]. Accordingly, k ratio was found to range between 1.04 and 1.57.…”
Section: Methodsmentioning
confidence: 99%
“…des Protokolls werden Endothelschädigungen i. d. R. jedoch nicht beobachtetauch bei der intensivierten und beschleunigten Bestrahlung oder der Verwendung hypotonen Riboflavins zur Quellung bei Hornhäuten < 400 μm (▶ Abb. 4) [36,81,95,130,134,146,[169][170][171][172][173]. Es ist unbedingt zu beachten, dass es bereits bei der Riboflavingabe zu einer Stromaverdünnung um bis zu 35 % kommen kann (osmotische Wirkung des Dextrans) [104,174,175].…”
Section: Veränderungen Nach Crosslinkingunclassified